Effects of Iron Species on Catalytic Performance for Phenol Hydroxylation of Fe-MCM-41 - Pantupho, Waenkaew; Deekamwong, Krittanun; Prayoonpokarach, Sanchai; Wittayakun, Jatuporn; Loiha, Sirinuch (KKU Science Journal, 2016)
Catalysts with 5 wt% iron supported on MCM-41 were prepared by impregnation (5Fe-MCM-41_IMP) and mixed gel hydrothermal synthesis (5Fe-MCM-41_HYD). Both catalysts showed high crystallinity of regular hexagonal structure of MCM-41. Iron species in 5Fe-MCM-41_IMP were the magnetite or inverse spinel Fe3O4 whereas that in 5Fe-MCM-41_HYD was tetrahedral Fe(III) in the MCM-41 framework. Catalytic activity and selectivity for phenol hydroxylation of the catalysts were determined. A higher catalytic activity of 5Fe-MCM-41_HYD over 5Fe-MCM-41_IMP was observed. Catalytic selectivities in term of catechol to hydroquinone ratio were 70:30 and 60:40 for 5Fe-MCM-41_IMP and 5Fe-MCM-41_HYD, respectively. The selectivity to hydroquinone was improved by the presence of tetrahedral Fe(III) in the MCM-41 framework due to its low hydrophilicity. The Fe3O4 species on 5Fe-MCM-41_IMP was more selective to catechol and favorable for strong adsorption of phenol due to its high hydrophilicity leading to catalytic deactivation by carbon deposition.